2017
DOI: 10.1159/000484255
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Urinary Alpha1-Microglobulin Levels and Nonalcoholic Fatty Liver Disease: A Cross-Sectional Study

Abstract: Background: We aimed to explore the association between urinary alpha1-microglobulin (A1M) levels and nonalcoholic fatty liver disease (NAFLD) in a Chinese population. Study: We performed a cross-sectional study among 2,215 Chinese who attended their annual health examination at First Affiliated Hospital, College of Medicine, Zhejiang University. Urinary A1M-creatinine ratio and other clinical and laboratory parameters were measured. Results: A total of 20.9% of subjects fulfilled the diagnostic cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…A cross-sectional study demonstrated a significant correlation between urinary α1m levels and MAFLD, suggesting its potential as a non-invasive diagnostic biomarker and a screening tool for identifying advanced fibrosis. Furthermore, these findings indicated that urinary α1m could also contribute to the early detection of kidney injury beyond eGFR [79]. However, the current study did not find significant changes in α1m/Cr levels in MAFLD patients following an intervention aimed at reducing IFC.…”
Section: Discussioncontrasting
confidence: 74%
“…A cross-sectional study demonstrated a significant correlation between urinary α1m levels and MAFLD, suggesting its potential as a non-invasive diagnostic biomarker and a screening tool for identifying advanced fibrosis. Furthermore, these findings indicated that urinary α1m could also contribute to the early detection of kidney injury beyond eGFR [79]. However, the current study did not find significant changes in α1m/Cr levels in MAFLD patients following an intervention aimed at reducing IFC.…”
Section: Discussioncontrasting
confidence: 74%
“…α1-Microglobulin (A1M) is a 26 kDa plasma and tissue protein, which is mainly synthesized in the liver, but also in smaller amounts in peripheral organs [85][86][87]. A crosssectional study showed a significant association between urinary A1M-creatinine ratio and NAFLD [88]. Hakuno et al have identified A1M as an Akt-activating hepatokine by screening the effects of conditioned media on doxorubicinor hypoxia-induced cardiomyocytes stress in vitro, and the in vivo study also confirmed that A1M is produced by the liver rather than the heart [89].…”
Section: Hepatokines Link the Liver Tomentioning
confidence: 99%
“…Patients with non-alcoholic fatty liver disease (NAFLD) tend to have high urinary α1MG levels. 9 NAFLD leads to liver complications, including non-alcoholic steatohepatitis, liver cirrhosis and hepatocellular carcinoma. 10 Metformin has benefits, such as inhibiting hepatic gluconeogenesis, modifying hepatic fatty acid metabolism and enhancing insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with non‐alcoholic fatty liver disease (NAFLD) tend to have high urinary α1MG levels 9 . NAFLD leads to liver complications, including non‐alcoholic steatohepatitis, liver cirrhosis and hepatocellular carcinoma 10 .…”
Section: Discussionmentioning
confidence: 99%